2017
DOI: 10.23865/njlr.v3.469
|View full text |Cite
|
Sign up to set email alerts
|

Interactional organization and pedagogic aims of reading aloud practices in L1 education

Abstract: The aim of this article is to examine the students' and teachers' activities of reading aloud as it occurs in and through interaction in L1-classrooms in the sixth grade with 12-year-old students. Our data consists of video-recorded classroom interaction in Finnish comprehensive schools. The method adopted is conversation analysis. This analysis encompasses read-alouds with reference to genre, source of the text and recipients' visual access or non-access to the text. According to our analysis, the reading alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…CA on reading aloud practices in schools has shown that interaction and attention are affected by several elements, such as whether the pupils have the text in front of them and the degree to which the teacher coordinates via embodied resources and explications (Tainio & Slotte, 2017). Interpreters can coordinate attention strategically by using gaze and/or explicitly asking the listener if the speed is adequate or if the reading is understandable.…”
Section: Safeguarding Attention and Agencymentioning
confidence: 99%
“…CA on reading aloud practices in schools has shown that interaction and attention are affected by several elements, such as whether the pupils have the text in front of them and the degree to which the teacher coordinates via embodied resources and explications (Tainio & Slotte, 2017). Interpreters can coordinate attention strategically by using gaze and/or explicitly asking the listener if the speed is adequate or if the reading is understandable.…”
Section: Safeguarding Attention and Agencymentioning
confidence: 99%
“…Reading is one of the skills that can be integrated easily with any program in teaching English to young learners (Linse & Nunan, 2005) Reading aloud can be the simplest way for young learners to deliver the reading experience between the students and the teacher to introduce literacy skills (Barrentine, 1996). Many studies have argued the benefits of reading aloud for English students, especially young learners (Burkins & Croft, 2010;Mantei & Kervin, 2018;Pentimonti & Justice, 2010;Tainio & Slotte, 2017). Besides, experts have argued the importance of reading aloud as foundations for children's later language development (Hahn, 2002;Jacobs, 2016;Tarim, 2015).…”
Section: Introductionmentioning
confidence: 99%